2018
DOI: 10.4103/sajc.sajc_240_17
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of European Organization for Research and Treatment for Cancer quality of life questionnaire-OV-28 module into Indian languages (Hindi and Marathi) to study quality of life of ovarian cancer patients from a tertiary care cancer center

Abstract: Aim:The aim is to translate and validate the European Organization for Research and Treatment for Cancer (EORTC) ovarian cancer (OC) module (OV-28) into Hindi and Marathi to use for patients and scientific community.Methods and Results:The EORTC OV-28 was translated into Hindi and Marathi languages using prescribed guidelines by the EORTC. The process included forward translation by four translators (2 each for Hindi and Marathi). The questionnaires obtained were then given to independent backward-translators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It should also be noted that in another randomized ovarian cancer study, the EORTC QLQ-OV28 module was designed without the use of these sexual function items (13) . Bajpai et al (14) also showed due to cultural taboos prevalent in India, people feel uncomfortable in talking about sexual behavior in general and a similar observation was noted when patients were asked to respond to question numbers 55-58 in the study of validation of EORTC QLQ-OV28 into Indian languages. The inconsistency of these items with the module has led to the placement of this subscale at the end of the module, so that it could be omitted without interfering with the other presented items.…”
Section: Discussionmentioning
confidence: 61%
“…It should also be noted that in another randomized ovarian cancer study, the EORTC QLQ-OV28 module was designed without the use of these sexual function items (13) . Bajpai et al (14) also showed due to cultural taboos prevalent in India, people feel uncomfortable in talking about sexual behavior in general and a similar observation was noted when patients were asked to respond to question numbers 55-58 in the study of validation of EORTC QLQ-OV28 into Indian languages. The inconsistency of these items with the module has led to the placement of this subscale at the end of the module, so that it could be omitted without interfering with the other presented items.…”
Section: Discussionmentioning
confidence: 61%
“…Confusion index is the most commonly used measure to evaluate a M.T. [25]. It is the probability of test data calculated according to the language model.…”
Section: Decoding Of Discontinuous Phrase Algorithmmentioning
confidence: 99%